Unravelling the Complex LiOH‐Based Cathode Chemistry in Lithium–Oxygen Batteries. (16th December 2022) - Zhang, Xiahui; Dong, Panpan; Noh, Seunghyo; Zhang, Xianghui; Cha, Younghwan; Ha, Su; Jang, Ji‐Hoon; Song, Min‐Kyu
Abstract: The LiOH‐based cathode chemistry has demonstrated potential for high‐energy Li−O2 batteries. However, the understanding of such complex chemistry remains incomplete. Herein, we use the combined experimental methods with ab initio calculations to study LiOH chemistry. We provide a unified reaction mechanism for LiOH formation during discharge via net 4 e − oxygen reduction, in which Li2 O2 acts as intermediate in low water‐content electrolyte but LiHO2 as intermediate in high water‐content electrolyte. Besides, LiOH decomposes via 1 e − oxidation during charge, generating surface‐reactive hydroxyl species that degrade organic electrolytes and generate protons. These protons lead to early removal of LiOH, followed by a new high‐potential charge plateau (1 e − water oxidation). At following cycles, these accumulated protons lead to a new high‐potential discharge plateau, corresponding to water formation. Our findings shed light on understanding of 4 e − cathode chemistries in metal–air batteries. Abstract : The complex LiOH chemistry is studied using experimental methods combined with ab initio calculations. During discharge, LiOH formation proceeds via 4 e − O2 reduction. During charge, LiOH oxidation proceeds via 1 e − oxidation to form OH*, followed by water oxidation and proton formation that leads to high‐potential discharge plateau at subsequent cycles.